2021
DOI: 10.1097/as9.0000000000000048
|View full text |Cite
|
Sign up to set email alerts
|

Where Did All the Appendicitis Go? Impact of the COVID-19 Pandemic on Volume, Management, and Outcomes of Acute Appendicitis in a Nationwide, Multicenter Analysis

Abstract: Objective: The study objective was to evaluate effects of the COVID-19 pandemic on rates of emergency department (ED) acute appendicitis presentation, management strategies, and patient outcomes. Summary Background Data: Acute appendicitis is the most commonly performed emergency surgery in the United States and is unlikely to improve without medical or surgical intervention. Dramatic reductions in ED visits prompted concern that individuals with seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…This twenty-seven-item scale has minimum and maximum scores of 0 and 32, respectively. On the basis of these scores, the risk of bias in each study was declared as high (score 0-15), moderate (score = [16][17][18][19][20][21][22][23], or low (score > 23). Subsequently, the inter-observer agreement on these scores was adjudged using the Kappa statistics [28].…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…This twenty-seven-item scale has minimum and maximum scores of 0 and 32, respectively. On the basis of these scores, the risk of bias in each study was declared as high (score 0-15), moderate (score = [16][17][18][19][20][21][22][23], or low (score > 23). Subsequently, the inter-observer agreement on these scores was adjudged using the Kappa statistics [28].…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…Despite the confinement measures, acute appendicitis does not quarantine [ 18 ]. The pandemic has impacted volume, diagnostic and management strategies, and patient outcomes of acute appendicitis [ 19 , 20 ]. A nationwide study in the United States found a significant decrease in acute appendicitis presentation, while two studies from Germany observed a decrease in the number of appendectomies during the lockdown [ 19 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, in the face of the pandemic, people were reluctant to leave their homes to seek medical care due to fears of contracting the virus within the hospital environment [11][12][13] and movement restrictions placed by different governments in a bid to contain the spread of the virus [8]. These led to delayed presentations and hence an increased risk of complications arising in the setting of acute appendicitis.…”
Section: Resultsmentioning
confidence: 99%